Entrepreneurship-Based Character Education: A Case Study of Strengthening the Pancasila and Rahmatan lil ‘Alamin Student Profile - Ilma, Putri Amelia Nur; Ulfa, Diana Lutfiana (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2025)
The rapid advancement of the digital era, marked by the rise of Generation Alpha and the concept of Society 5.0, has challenged educators to reinforce students’ moral and spiritual foundations alongside academic competence. This study explores how entrepreneurship-based learning can be used as a medium to strengthen the Pancasila Student Profile and the Rahmatan lil ‘Alamin values among elementary students. Using a qualitative case study design, the research was conducted at MIN 9 Blitar, involving the principal, curriculum coordinator, four teachers, and five sixth-grade students selected through purposive sampling. Data were gathered through classroom observations, semi-structured interviews, and document analysis, and analyzed using the interactive model of Miles and Huberman with data triangulation to ensure validity. The findings reveal that the entrepreneurship project encouraged students to apply values of independence, creativity, cooperation, and compassion through the production of banana-based products. The learning process helped internalize moral and civic virtues embedded in the Pancasila principles and Rahmatan lil ‘Alamin ethos. However, variations in students’ engagement and limited community collaboration emerged as challenges for program sustainability. This study demonstrates that entrepreneurship-oriented projects can serve as an effective approach for integrating character and faith-based education in primary schools, provided that continuous mentoring and structured evaluation are maintained.nce for education policymakers to expand the implementation of similar projects on a larger scale.